Sphenopalatine ganglion pulsed radiofrequency treatment in patients suffering from chronic face and head pain - Mert Akbas; Emel Gunduz; Suat Sanli; Arif Yegin (Brazilian Journal of Anesthesiology, 2016)
Purpose: There are various facial pain syndromes including trigeminal neuralgia, trigeminal neuropathic pain and atypical facial pain syndromes. Effectiveness of the pulsed radiofrequency in managing various pain syndromes has been clearly demonstrated. There are a limited number of studies on the pulsed radiofrequency treatment for sphenopalatine ganglion in patients suffering from face and head pain. The purpose of this study is to evaluate the satisfaction of pulsed radiofrequency treatment at our patients retrospectively. Methods: Infrazygomatic approach was used for the pulsed radiofrequency of the sphenopalatine ganglion under fluoroscopic guidance. After the tip of the needle reached the target point, 0.25–0.5 ms pulse width was applied for sensory stimulation at frequencies from 50 Hz to 1 V. Paraesthesias were exposed at the roof of the nose at 0.5–0.7 V. To rule out trigeminal contact that led to rhythmic mandibular contraction, motor stimulation at a frequency of 2 Hz was applied. Then, four cycles of pulsed radiofrequency lesioning were performed for 120 s at a temperature of 42 °C. Results: Pain relief could not be achieved in 23% of the patients (unacceptable), whereas pain was completely relieved in 35% of the patients (excellent) and mild to moderate pain relief could be achieved in 42% of the patients (good) through sphenopalatine ganglion-pulsed radiofrequency treatment. Conclusion: Pulsed radiofrequency of the sphenopalatine ganglion is effective in treating the patients suffering from intractable chronic facial and head pain as shown by our findings. There is a need for prospective, randomized, controlled trials in order to confirm the efficacy and safety of this new treatment modality in chronic head and face pain. Resumo: Objetivo: Existem várias síndromes de dor facial, incluindo neuralgia trigeminal, dor neuropática trigeminal e síndromes atípicas de dor facial. A eficácia da radiofrequência pulsada (RFP) para o manejo de várias síndromes de dor foi claramente demonstrada. Há um número limitado de estudos sobre o tratamento com RFP para gânglio esfenopalatino (GEP) em pacientes que sofrem de dor facial e de cabeça. O objetivo deste estudo foi avaliar a satisfação do tratamento com PRF em nossos pacientes, retrospectivamente.. Métodos: A abordagem infrazigomática foi usada para a RFP do GEP sob orientação fluoroscópica. Depois de a ponta da agulha atingir o ponto alvo, pulsos de 0,25 a 0,5 ms foram aplicados para a estimulação sensorial em frequências de 50 Hz a 1 V. Parestesias foram expostas no teto do nariz em 0,5 a 0,7 V. Para excluir o contato trigeminal que levou à contração mandibular rítmica, a estimulação motora foi aplicada na frequência de 2 Hz. Em seguida, quatro ciclos de RFP foram realizados durante 120 segundos a uma temperatura de 42 ̊C. Resultados: O alívio da dor não foi obtido em 23% dos pacientes (inaceitável); enquanto a dor foi totalmente aliviada em 35% dos pacientes (excelente) e o alívio de leve a moderado da dor foi obtido em 42% dos pacientes (bom), com o tratamento RFP-GEP. Conclusão: RFP para GEP é eficaz no tratamento de pacientes que sofrem de dor crónica intratável, facial e de cabeça, como mostrado por nossas descobertas. Estudos prospectivos, randômicos e controlados são necessários para confirmar a eficácia e segurança dessa nova modalidade de tratamento para dor crônica facial e de cabeça. Keywords: Sphenopalatine ganglion, Pulsed radiofrequency, Chronic face and head pain, Palavras-chave: Gânglio esfenopalatino, Radiofrequência pulsada, Dor crônica facial e de cabeça